Asymptotic properties of maximum-likelihood estimators for Heston models based on continuous time observations. Issue 2 (3rd March 2016) - Barczy, Mátyás; Pap, Gyula
Abstract : We study asymptotic properties of maximum-likelihood estimators for Heston models based on continuous time observations of the log-price process. We distinguish three cases: subcritical (also called ergodic), critical and supercritical. In the subcritical case, asymptotic normality is proved for all the parameters, while in the critical and supercritical cases, non-standard asymptotic behaviour is described.